Odotype, the olfactory identity of a brand - Rodríguez-Díaz, María Alejandra (2020)
Smell is one of the least used senses in advertising and/or marketing strategies. This study analyzes the conditions for the implementation of the odotype in the brand identity. A qualitative research approach and Grounded Theory method are using to develop an explanatory theory about the concept “odotype”. A semi-structured interview guide was designed according to the categories proposed in the research: odotype and brand identity. This research shows that odotype and sensorial marketing are different concepts; providing a definition for each concept. The Peruvian market is still at an early stage with respect to the aroma and odotype.